Circularly polarized light-emitting multilayer assembly film and preparation method thereof
By adopting the multi-layer assembly strategy of "matching rules" in circularly polarized luminescent materials and deflection stacking of one-dimensional metal nanomaterials, the difficulties in existing materials in CPL regulation and multi-color CPL implementation are solved, and efficient and multi-parameters are achieved Regulated circularly polarized luminescent multi-layer assembly film.
Patent Information
- Application Number
- CN202411941273.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing chiral molecules and supramolecular materials have weak glum values in circular polarization luminescence (CPL), and are difficult and complex to regulate CPL, making it difficult to obtain multi-color CPL covering multiple bands.
By adopting a multi-layer assembly strategy of "matching rules", the fluorescent layer and optically active layer are stacked, and deflected stacking is used to deflect and stack the orientation axis direction of one-dimensional metal nanomaterials to achieve full parameter regulation of CPL wavelength, intensity and rotation direction.
It achieves high CPL strength (>1000 mdeg) and high glum (>0.3), multi-color and white CPL that can cover the entire visible area color segment, with excellent heat resistance and environmental durability.
Smart Images

Figure CN119439355A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of circularly polarized luminescent chiral thin film materials, and relates to a circularly polarized luminescent multilayer assembly film having multicolor properties and high efficiency controllability and a preparation method thereof. Background Art
[0002] Chiral optical materials play an increasingly important role in polarization display, information encryption, and smart sensing due to their unique ability to regulate the circular polarization of light (including circularly polarized absorption (CD) and circularly polarized luminescence (CPL)). Compared with conventional fluorescent materials, CPL materials can significantly improve information security because they can deeply modulate fluorescence in a higher-dimensional polarization state. However, this also puts higher requirements on the basic performance of CPL materials, such as: high luminescence asymmetry factor ( g lum ), multicolor CPL, excellent environmental stability, etc. In recent years, researchers have done a lot of research on circularly polarized luminescent materials, including chiral organic small molecules, chiral inorganic nanoparticles, supramolecular assemblies and bulk films ( CCS Chem. 2024, 6, 518-527, Angew. Chem. Int. Ed. 2024, e202407385 ). However, for most chiral molecules and even supramolecular materials, the available g lum Values are usually weak (10 -4 -10 -2 ), and the regulation of CPL is difficult and complicated. In addition, it is relatively difficult to obtain multi-color CPL covering multiple bands.
[0003] Using the "matching rule" multilayer assembly strategy, CPL can be easily and efficiently obtained by utilizing the overlap of the emission-absorption bands of the fluorescent layer and the chiral layer without any chemical interaction between the two ( Macromolecules 2019, 52, 376-384 This strategy breaks the shortcomings of the traditional use of chemical / physical interactions to construct CPL materials, which are complex and poorly controllable, making the design and preparation of CPL materials simpler and richer. At present, the CPL materials prepared based on this rule g lum Can reach 10 -1 However, since the chirality comes from intrinsic chiral raw materials such as chiral polymers and supramolecular materials, it is still impossible to efficiently adjust the CPL characteristic parameters such as sign, intensity, and wavelength. In addition, higher CPL can be obtained by assembling fluorescent dye molecules with cholesteric liquid crystals (such as cellulose nanocrystals CNC) layer by layer. g lum (>10 0). However, the inherent environmental stability of liquid crystal materials is poor (such as water resistance and high temperature resistance), which is not conducive to its application in many practical scenarios. Secondly, due to the inherent chirality type (left-handed structure) formed by cholesteric phase liquid crystal during the assembly process, the direction of CPL is difficult to adjust (only right-handed CPL is produced). Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a circularly polarized luminescent multilayer assembly film and a preparation method thereof, wherein the circularly polarized luminescent multilayer assembly film can achieve full parameter control of CPL wavelength (ie, color), intensity and handedness.
[0005] The present invention is achieved through the following technical solutions: A circularly polarized luminescent multilayer assembled film comprises a fluorescent layer and an optically active layer stacked together; the fluorescent layer comprises a first flexible polymer film and a fluorescent dye distributed in the first flexible polymer film; the optically active layer comprises at least two layers of hybrid oriented films, the hybrid oriented films comprise a second flexible polymer film and a one-dimensional metal nanomaterial distributed in the second flexible polymer film and arranged in an oriented manner, the second flexible polymer film and the one-dimensional metal nanomaterial are both achiral; each layer of the hybrid oriented film is stacked and arranged at a preset deflection angle along the orientation axis direction of the one-dimensional metal nanomaterial.
[0006] Preferably, the fluorescent dye is Nile red, coumarin, fluoroborate dipyrrolidone or rhodamine.
[0007] Preferably, the first flexible polymer film is a polymethyl methacrylate film or a polyvinyl alcohol film, and the second flexible polymer film is a polyvinyl alcohol film.
[0008] Preferably, the mass of the fluorescent dye accounts for 0.01% to 1% of the mass of the first flexible polymer film.
[0009] Preferably, the mass of the one-dimensional metal nanomaterial accounts for 0.08% to 0.24% of the mass of the second flexible polymer film.
[0010] Preferably, the one-dimensional metal nanomaterial is gold or silver.
[0011] Preferably, the one-dimensional metal nanomaterial has a morphology of nanorods or nanowires.
[0012] Preferably, the deflection angle between the uppermost hybrid alignment film and the lowermost hybrid alignment film is in the range of 0° to ±180°, and is not 0°±A90°, where A is a constant.
[0013] The method for preparing the circularly polarized luminescent multilayer assembly film of the present invention comprises: Mixing a fluorescent dye and a first polymer in a solvent to obtain a first mixed solution; drying the first mixed solution to form a film to obtain a fluorescent layer; Mixing a second polymer and a one-dimensional metal nanomaterial in a solvent to obtain a second blend solution; drying the second blend solution to form a film to obtain a hybrid film; axially stretching the hybrid film in one direction at a preset stretching ratio to obtain a hybrid oriented film; stacking a plurality of the hybrid oriented films at a preset deflection angle along the orientation axis direction to obtain an optically active layer; The fluorescent layer and the optically active layer are stacked together in sequence to obtain a circularly polarized luminescent multilayer assembly film.
[0014] Preferably, the preset draft ratio is 100% to 500%.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The circularly polarized luminescent multilayer assembled film of the present invention does not rely on any chiral template. It is based on completely non-chiral building units, utilizes single-layer orientation, and is assembled layer by layer according to "matching rules" to obtain a highly efficient method of twisted stacking. The CPL of the circularly polarized luminescent multilayer assembled film of the present invention is generated by the optical coupling of the fluorescent layer and the optically active layer. The fluorescent layer is first excited by ultraviolet light to produce fluorescent color. The optically active layer can selectively absorb left-handed / right-handed fluorescence of the corresponding band, and output the corresponding right-handed / left-handed fluorescence to achieve circularly polarized luminescence. The one-dimensional metal nanomaterial is evenly distributed in the second flexible polymer film instead of being aggregated and distributed on the surface of the film, so that the CD peak band of the optically active layer matches the band emitted by the fluorescent layer, thereby obtaining a circularly polarized luminescent multilayer assembled film with high CPL intensity. The circularly polarized luminescent multilayer assembled film of the present invention has high CPL intensity (>1000 mdeg), high g lum (>0.3), by selecting fluorescent layers with different emission wavelengths, multi-color and white CPL covering the entire visible color range can be achieved. By adjusting the content and deflection angle of fluorescent dyes and one-dimensional metal nanomaterials, the characteristic parameters such as the direction and size of CPL can be simply and efficiently regulated. In addition, the circularly polarized luminescent multilayer assembly film also has excellent heat stability, and the maximum operating temperature reaches 110°C without any effect on its optical properties. It also has excellent light resistance and environmental durability. After 72 hours of UV-365nm light irradiation and 50 days in the environment, the CPL spectrum of the circularly polarized luminescent multilayer assembly film has almost no change. Finally, the excellent mechanical properties (tensile strength: 216MPa, elongation at break: 27%) of the circularly polarized luminescent multilayer assembly film will also greatly enhance the basic performance and application range of the material.
[0016] Furthermore, by selecting fluorescent dyes with different emission wavelengths, the CPL color of the circularly polarized luminescent multilayer assembly film can be adjusted to obtain circularly polarized luminescent multilayer assembly films with different CPL colors.
[0017] Furthermore, by regulating the content of fluorescent dyes and one-dimensional metal nanomaterials, the CPL intensity of the circularly polarized luminescent multilayer assembled film can be regulated.
[0018] Furthermore, the rotational regulation of the deflection angle of the hybrid oriented film can realize the control of the intensity and direction (left-handed / right-handed) of the circularly polarized luminescent multilayer assembled film CPL.
[0019] The preparation method of the circularly polarized luminescent multilayer assembly film of the present invention is simple, low-cost, and highly universal, and has great application potential in the fields of information encryption, polarization display, and the like in the future.
[0020] Furthermore, the regulation of the orientation degree (stretching ratio) in the hybrid oriented film can achieve the control of the CPL intensity. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is a SEM image of the PVA-AuNRs hybrid film after axial stretching described in Example 1 of the present invention.
[0023] Figure 2 Polarization extinction spectra of PVA-AuNRs stacked films at different deflection angles (a) and statistics of extinction intensity changing with deflection angle (b).
[0024] Figure 3 It is the CD spectrum corresponding to the PVA-AuNRs stacked film described in Example 1 of the present invention at different interlayer angles (±15°, ±30°, ±45°).
[0025] Figure 4 The CD spectrum (a) of the PVA-AuNRs stacked film obtained by surface coating of AuNR solution in Comparative Example 1 and the CPL spectrum (b) of its circularly polarized luminescent multilayer assembled film.
[0026] Figure 5 The fluorescence emission spectra (a) of the different fluorescent layers described in Example 2 of the present invention and the fluorescence color picture (b) of the corresponding fluorescent solution under 365nm ultraviolet excitation.
[0027] Figure 6 The CPL spectra (a) and the CPL intensity and direction variation statistics (b) of the circularly polarized luminescent multilayer assembled films prepared from PVA-AuNRs stacked films with different deflection angles (±15°, ±30°, ±45°) in Example 3 of the present invention.
[0028] Figure 7 It is the CPL spectrum of the circularly polarized luminescent multilayer assembled film based on the assembly of different fluorescent layers and PVA-AuNRs stacked films in Example 4 of the present invention.
[0029] Figure 8 The CPL spectrum changes at different operating temperatures of the circularly polarized luminescent multilayer assembled film assembled by the present invention using a Nile red fluorescent layer and a PVA-AuNRs stacked film with an angle of -30°.
[0030] Fig. 9 It is the CPL spectrum change of the circularly polarized luminescent multilayer assembly film obtained by the present invention under different UV-365nm irradiation time.
[0031] Fig.10 The CPL spectrum changes of the circularly polarized luminescent multilayer assembled film obtained by the present invention when placed in a standard environment (RH=50%, T=25°C) for different time periods.
[0032] Fig.11 It is the stress-strain curve of the single-layer PVA-AuNRs stacked film of the present invention with a stretching ratio of 450% and a physical picture showing its bendability and flexibility.
[0033] Fig.12 These are the CPL spectra of circularly polarized luminescent multilayer assembled films with different fluorescent dye contents in Example 5 (a), the CPL spectra of circularly polarized luminescent multilayer assembled films with different AuNRs contents in Example 6 (b), and the CPL spectra of circularly polarized luminescent multilayer assembled films with different stretching ratios in Example 7 (c). DETAILED DESCRIPTION
[0034] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0035] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0036] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0037] In addition, it should be noted that the terms "first", "second", etc. of the present invention are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described here can be implemented in an order other than those illustrated or described here. The orientation or position relationship indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention; in addition, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection or a detachable connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two elements.
[0038] The circularly polarized luminescent multilayer assembled film of the present invention comprises a fluorescent layer and an optically active layer stacked together; the fluorescent layer comprises a first flexible polymer film and a fluorescent dye distributed in the first flexible polymer film; the optically active layer comprises at least two layers of hybrid oriented films, the hybrid oriented film comprises a second flexible polymer film and a one-dimensional metal nanomaterial distributed in the second flexible polymer film matrix and arranged in an oriented manner, the second flexible polymer film and the one-dimensional metal nanomaterial are both non-chiral; each layer of the hybrid oriented film is stacked and arranged at a preset deflection angle along the orientation axis direction of the one-dimensional metal nanomaterial.
[0039] In the present invention, the deflection angle between the topmost hybrid oriented film and the bottommost hybrid oriented film is in the range of 0° to ±180°, and is not 0°±A90°, where A is a constant. Preferably, each layer of the hybrid oriented film deflects in a clockwise direction or in a counterclockwise direction.
[0040] In the circularly polarized luminescent multilayer assembled film of the present invention, the mass of the fluorescent dye accounts for 0.01% to 1% of the mass of the first flexible polymer film; the mass of the one-dimensional metal nanomaterial accounts for 0.08% to 0.24% of the mass of the second flexible polymer film. The content of the fluorescent dye will affect the intensity of FL and thus affect CPL, and the amount of gold nanorods used will affect the CD intensity and thus affect CPL.
[0041] The fluorescent dye in the fluorescent layer of the present invention can be a common commercial fluorescent dye, such as Nile Red, rhodamine, coumarin, BODIPY. In specific implementation, the fluorescent dye with the corresponding emission wavelength is selected according to the required fluorescent color.
[0042] The first flexible polymer film for loading the fluorescent dye in the present invention may be a polymethyl methacrylate (PMMA) or polyvinyl alcohol (PVA) film.
[0043] The optically active layer of the present invention preferably adopts a PVA-AuNRs stacked film, and the PVA-AuNRs stacked film is obtained by stacking at least two layers of PVA-AuNRs hybrid oriented films at a preset deflection angle along the orientation axis direction of the one-dimensional metal nanomaterial. The PVA-AuNRs hybrid oriented film is obtained by wet stretching a PVA-AuNRs hybrid film of a certain thickness obtained by casting and then drying and shaping. Among them, the PVA-AuNRs hybrid film is obtained by physically blending an AuNRs solution and a PVA solution in a certain proportion, and then drying to form a film.
[0044] In a specific embodiment of the present invention, the aspect ratio of AuNRs is preferably 1-4, and the aspect ratio is not 1 and 4, but preferably 2.
[0045] The circularly polarized luminescent multilayer assembled film of the present invention is prepared by: Mixing a fluorescent dye and a first polymer in a solvent to obtain a first mixed solution; drying the first mixed solution to form a film to obtain a fluorescent layer; Mixing a second polymer and a one-dimensional metal nanomaterial in a solvent to obtain a second blend solution; drying the second blend solution to form a film to obtain a hybrid film; axially stretching the hybrid film in one direction at a preset stretching ratio to obtain a hybrid oriented film; stacking a plurality of the hybrid oriented films at a preset deflection angle along the orientation axis direction to obtain an optically active layer; The fluorescent layer and the optically active layer are stacked together to obtain a circularly polarized luminescent multilayer assembly film.
[0046] As a preferred embodiment, the specific preparation method of the circularly polarized luminescent multilayer assembly film of the present invention comprises the following steps: (1) Preparation of fluorescent layer: According to the required fluorescent color, take the fluorescent dye with the corresponding emission wavelength, stir and dissolve it in dichloromethane or water at room temperature to obtain a fluorescent dye solution of a certain concentration. Then weigh a certain amount of PMMA or PVA solution and blend it with the fluorescent dye solution in a certain proportion. Finally, pour a certain mass of the blended solution into a culture dish and put it in an oven to dry into a film.
[0047] (2) Preparation of PVA-AuNRs hybrid membrane: The AuNRs solution and the PVA solution were physically blended to obtain a uniform PVA-AuNRs solution. A certain mass of the blended solution was poured into a culture dish and placed in an oven to dry into a membrane.
[0048] (3) Preparation of PVA-AuNRs hybrid oriented film: The PVA-AuNRs hybrid film was cut into rectangles and clamped on the two side chucks of a homemade stretching device. After the hybrid film was fully wetted with pure water, it was axially stretched at a certain stretching ratio (100%~500%) and finally dried and shaped to obtain a PVA-AuNRs hybrid oriented film with a certain degree of orientation.
[0049] (4) Preparing a PVA-AuNRs stacked film: Take two or more PVA-AuNRs hybrid oriented films with a certain degree of orientation prepared in step (3), and stack them along their axial orientation direction at a certain deflection angle (for example, 0°, ±15°, ±30°, ±45°) to obtain a PVA-AuNRs stacked film with a certain optical activity.
[0050] (5) Preparation of circularly polarized luminescent multilayer assembled film: The fluorescent layer of the required color segment and the PVA-AuNRs stacked film are stacked layer by layer to obtain a circularly polarized luminescent multilayer assembled film.
[0051] When in use, the fluorescent layer is placed in front of the excitation light path. When ultraviolet light excites the fluorescent layer to produce corresponding fluorescence, the optically active layer selectively absorbs the fluorescence to obtain circularly polarized luminescence.
[0052] Efficient regulation of the circularly polarized luminescent multilayer assembled film CPL: First, the CPL color can be regulated by adjusting the fluorescence emission wavelength, thereby achieving the purpose of multi-color CPL mentioned above; secondly, the CPL intensity can be regulated by regulating the fluorescence intensity of the fluorescent layer, and the fluorescence intensity can be controlled by the content of the fluorescent dye. Thirdly, the rotational regulation of the deflection angle of the hybrid oriented film can control the CPL intensity and direction (left-handed / right-handed). The regulation of the AuNRs content in the hybrid oriented film and the orientation degree (stretching ratio) of the hybrid film can also control the CPL intensity. Finally, the CPL response band of the material can be controlled by regulating the aspect ratio of the AuNRs in the hybrid oriented film.
[0053] In the embodiment of the present invention, the basic optical activity (including CPL intensity, glum, coverage wavelength width, etc.) of the obtained circularly polarized light-emitting film is characterized by using a commercial CPL spectrum.
[0054] Example 1 Stacked films with different deflection angles Weigh 5g of PVA particles and pour them into 95g of pure water. Heat at 90℃ and stir magnetically at 1500r / min for 3h. After the particles are completely dissolved, a PVA solution with a solid content of 5wt% is obtained. Weigh 20g of the prepared PVA solution and physically blend it with 25mL of AuNRs solution with a certain concentration (0.1mg / mL) and an aspect ratio of 2. Stir magnetically for 12h (1500rpm) to obtain a PVA-AuNRs solution. Pour the obtained PVA-AuNRs solution into a 10cm×10cm culture dish and dry it in a 45℃ oven. After drying and forming a film, a uniform PVA-AuNRs hybrid film with a thickness of about 100μm is obtained.
[0055] The PVA-AuNRs hybrid film was cut into 4×1.5cm rectangular strips, and the two ends were clamped on the stretching device. The middle 1.5cm width area of the rectangular strip was fully moistened with pure water and then axially stretched at a rate of 450%. Finally, the water was evaporated and dried to form an anisotropic PVA-AuNRs hybrid oriented film with a certain degree of orientation. Two PVA-AuNRs hybrid oriented films were stacked along the axial direction at deflection angles of 0°, ±15°, ±30°, and ±45° (the orientation direction of the upper film relative to the lower film was specified to be positive (+) when rotated clockwise, and negative (-) when rotated counterclockwise), and finally a double-layer stacked PVA-AuNRs stacked film with different deflection angles was obtained.
[0056] Example 2 Fluorescent solutions and fluorescent layers of different fluorescent colors Weigh 10 mg of commercial Nile Red-625 nm (FL-625 nm) dye powder and dissolve it in 10 g of DCM (dichloromethane) to obtain a Nile Red dye solution with a concentration of about 0.1%. For dyes with different fluorescence emission wavelengths (coumarin 120-440 nm, coumarin 151-490 nm, coumarin 153-530 nm, pyrrole boron BODIPY-560 nm, rhodamine-6G-585 nm), they are prepared into corresponding fluorescent solutions according to the same concentration with the solvents (water / DCM) in which they can be dissolved. Specifically, rhodamine-6G-585 nm is dissolved in 10 g of water, and other coumarin 120-440 nm, coumarin 151-490 nm, coumarin 153-530 nm, pyrrole boron BODIPY-560 nm are all dissolved in DCM.
[0057] Take 2 mL of each fluorescent solution (coumarin 120-440 nm, coumarin 151-490 nm, coumarin 153-530 nm, pyrrole boron BODIPY-560 nm, Nile Red-625 nm) with a concentration of about 0.1% and blend it with 20 g of the prepared polymethyl methacrylate PMMA solution with a concentration of 5 wt% to obtain a uniform blended solution, pour it into a 10 cm × 10 cm Petri dish, put it in a 45 ° C oven to dry, and peel it off after the film is completely dry for use. Take 2 mL of the fluorescent solution of rhodamine-6G-585 nm with a concentration of about 0.1% and blend it with 20 g of the prepared polyvinyl alcohol PVA solution with a concentration of 5 wt% to obtain a uniform blended solution, pour it into a 10 cm × 10 cm Petri dish, put it in a 45 ° C oven to dry, and peel it off after the film is completely dry for use.
[0058] Through this embodiment, fluorescent layers formed by Nile Red-625 nm, coumarin 120-440 nm, coumarin 151-490 nm, coumarin 153-530 nm, BODIPY-560 nm, and Rhodamine-6G-585 nm were obtained, which were sequentially recorded as: the first fluorescent layer, the second fluorescent layer, the third fluorescent layer, the fourth fluorescent layer, the fifth fluorescent layer, and the sixth fluorescent layer.
[0059] Example 3 Circularly polarized luminescent multilayer assembled films obtained by stacking films at different deflection angles The first fluorescent layer formed by Nile Red-625nm in Example 2 and the PVA-AuNRs stacked films with different deflection angles obtained in Example 1 are stacked and assembled respectively to obtain a circularly polarized luminescent multilayer assembled film containing PVA-AuNRs stacked films with different deflection angles.
[0060] The red fluorescence emitted by the Nile Red fluorescent film was used as the fluorescence source of the circularly polarized luminescent multilayer assembled film, and the fluorescent layer was used as the upper layer incident with the excitation light source to characterize the CPL of each circularly polarized luminescent multilayer assembled film.
[0061] Example 4 Circularly polarized luminescent multilayer assembled films in different fluorescence emission bands The first fluorescent layer, the second fluorescent layer, the third fluorescent layer, the fourth fluorescent layer, the fifth fluorescent layer, and the sixth fluorescent layer with different fluorescent colors obtained in Example 2 were assembled with PVA-AuNRs stacked films with a deflection angle of ±45° to obtain circularly polarized luminescent multilayer assembled films with different emission bands. The CPL of the circularly polarized luminescent multilayer assembled film was characterized by using a CPL spectrometer.
[0062] Example 5 Circularly polarized luminescent multilayer assembled films with different fluorescent dye contents Weigh 10 mg of commercial Nile Red-625 nm dye powder and dissolve it in 10 g of DCM (dichloromethane) to obtain a Nile Red dye solution with a concentration of about 0.1%.
[0063] 0.1 mL, 1 mL, and 10 mL of a Nile red dye solution with a concentration of about 0.1% were taken, respectively, and mixed with 20 g of a prepared polymethyl methacrylate (PMMA) solution with a concentration of 5 wt% to obtain a uniform blended solution, which was poured into a 10 cm × 10 cm culture dish and placed in a 45°C oven to dry. After the film was completely dry, it was peeled off and set aside to obtain fluorescent layers with a fluorescent dye mass content of 0.01%, 0.1%, and 1%, respectively.
[0064] The fluorescent layers with different fluorescent dye contents mentioned above were respectively assembled with the PVA-AuNRs stacked films with a deflection angle of ±45° in Example 1 to form circularly polarized luminescent multilayer assembled films.
[0065] Example 6 Circularly polarized luminescent multilayer assembled films with different AuNR contents Weigh 5g of PVA particles and pour them into 95g of pure water. Heat at 90℃ and stir magnetically at 1500r / min for 3h. After the particles are completely dissolved, a PVA solution with a solid content of 5wt% is obtained. Weigh 20g of the prepared PVA solution and physically blend it with 8mL, 16mL, and 24mL of AuNRs solution with a concentration of 0.1mg / mL and an aspect ratio of 2, respectively. Stir magnetically for 12h (1500rpm) to obtain a PVA-AuNRs solution. Pour the obtained PVA-AuNRs solution into a 10cm×10cm culture dish and dry it in a 45℃ oven. After drying and forming a film, PVA-AuNRs hybrid films with AuNR contents of 0.08%, 0.16%, and 0.24% are obtained.
[0066] The PVA-AuNRs hybrid film was cut into 4×1.5cm rectangular strips, and the two ends were clamped on the stretching device. The middle 1.5cm width area of the rectangular strip was fully moistened with pure water and then axially stretched at a rate of 450%. Finally, the water was evaporated and dried to form an anisotropic PVA-AuNRs hybrid oriented film with a certain degree of orientation. Two PVA-AuNRs hybrid oriented films were stacked along the axial direction at a deflection angle of ±45°, and finally PVA-AuNRs stacked films with AuNRs contents of 0.08%, 0.16%, and 0.24% were obtained.
[0067] The first fluorescent layer formed by Nile Red-625nm in Example 2 was assembled with the PVA-AuNRs stacked films with different AuNRs contents in Example 6 to form a circularly polarized luminescent multilayer assembled film.
[0068] Example 7 PVA-AuNRs stacked films with different stretching ratios Weigh 5g of PVA particles and pour them into 95g of pure water. Heat at 90℃ and stir magnetically at 1500r / min for 3h. After the particles are completely dissolved, a PVA solution with a solid content of 5wt% is obtained. Weigh 20g of the prepared PVA solution and physically blend it with 25mL of AuNRs solution with a concentration of 0.1mg / mL and an aspect ratio of 2. Stir magnetically for 12h (1500rpm) to obtain a PVA-AuNRs solution. Pour the obtained PVA-AuNRs solution into a 10cm×10cm culture dish and dry it in a 45℃ oven. After drying and forming a film, a PVA-AuNRs hybrid film is obtained.
[0069] The PVA-AuNRs hybrid film was cut into 4×1.5cm rectangular strips, and the two ends were clamped on the stretching device. The middle 1.5cm width area of the rectangular strip was fully moistened with pure water and then axially stretched at 200%, 350%, and 500% respectively. Finally, the water was evaporated and dried to form anisotropic PVA-AuNRs hybrid oriented films with different orientation degrees were obtained. The PVA-AuNRs hybrid oriented films with the same orientation degree were stacked in pairs at a deflection angle of ±45° along the axial direction, and finally PVA-AuNRs stacked films with different optical activities were obtained.
[0070] The first fluorescent layer formed by Nile Red-625nm in Example 2 was assembled with the PVA-AuNRs stacked films with different stretching ratios in Example 7 to form a circularly polarized luminescent multilayer assembled film.
[0071] Comparative Example 1 Weigh 5g of PVA particles and pour them into 95g of pure water. Heat at 90℃ and stir them magnetically at 1500r / min for 3h until the particles are completely dissolved to obtain a PVA solution with a solid content of 5%. Weigh 20g of the prepared PVA solution and pour it into a 10cm×10cm petri dish and put it into a 45℃ oven to dry. After drying and forming a film, a PVA film is obtained.
[0072] 6 mL of AuNRs solution with a concentration of 0.1 mg / mL and an aspect ratio of 2 was drop-coated on the surface of the PVA film. After the solvent was fully evaporated, a PVA-AuNRs hybrid film was obtained.
[0073] The PVA-AuNRs hybrid film was cut into 4×1.5cm rectangular strips, and the two ends were clamped on the stretching device. The middle 1.5cm width area of the rectangular strip was fully moistened with pure water and then axially stretched at a rate of 450%. Finally, the water was evaporated and dried to form an anisotropic PVA-AuNRs hybrid oriented film with a certain degree of orientation. Two PVA-AuNRs hybrid oriented films were stacked along the axial direction at a deflection angle of ±45°, and finally a PVA-AuNRs stacked film with a certain optical activity was obtained.
[0074] Figure 1 This is the distribution of gold nanorods on the surface of the PVA-AuNRs hybrid film after axial stretching described in the present invention. It can be seen from the figure that the dispersed AuNRs after stretching are arranged in an orderly manner along the stretching direction. Since they are dispersed in the entire PVA film matrix, the surface content of the PVA-AuNRs hybrid film photographed by the electron scanning electron microscope is relatively small and the density is not high.
[0075] Figure 2 Figure a shows the polarization extinction spectra of the PVA-AuNRs hybrid oriented film at different deflection angles. Due to the uniform and non-aggregated distribution of AuNRs in the PVA film, the absorption peak has hardly changed relative to the wavelength of the AuNRs solution. The inset shows the relative direction of the linearly polarized light and the arrangement of the AuNRs. Figure 2 As can be seen in Figure b, due to its anisotropic structure, the extinction intensity of the PVA-AuNRs hybrid oriented film changes periodically with the deflection angle (wavelength 650 nm). Due to the isotropic structure of the non-oriented PVA-AuNRs hybrid film, its extinction intensity hardly changes with the deflection angle. Figure 2 The inset in b is the corresponding polar coordinate plot.
[0076] Figure 3 The CD spectra of the PVA-AuNRs stacked films with different deflection angles (±15°, ±30°, ±45°) described in Example 1 of the present invention are shown in FIG. Figure 3 As can be seen in a, the CD peak band is Figure 2 The absorption band in the film is consistent, and this band also matches the subsequent emission band of the fluorescent layer. It can be seen that due to the structural advantage of the twisted stacking of the PVA-AuNRs oriented hybrid film, the intensity and direction of the CD signal can be adjusted by simply adjusting the deflection angle between the layers. Figure 3 (b) in the figure is the statistical value of the CD intensity changing with the angle, and an effective fit is obtained using the sine function.
[0077] Figure 4 This is the CD spectrum of the PVA-AuNRs stacked film obtained by surface coating of AuNRs solution in Comparative Example 1. Figure 4As can be seen in a, due to the aggregation of AuNRs, the strongest CD peak band of this structure is significantly red-shifted to the infrared band (700-1600nm), which is almost not matched with the emission band of the fluorescent layer used later. The intensity of the corresponding circularly polarized luminescent multilayer assembly film obtained by the "matching rule" is extremely low ( Figure 4 (b)
[0078] Figure 5 The fluorescence emission spectra (a) of different fluorescent layers described in Example 2 of the present invention and the fluorescence colors (b) of corresponding fluorescent solutions under 365nm ultraviolet excitation are shown in the figure. The figure shows that fluorescent components (including fluorescent layers and fluorescent solutions) with different fluorescent colors covering the entire visible light band (380-780nm) can be prepared.
[0079] Figure 6 : is the CPL spectrum of the circularly polarized luminescent multilayer assembled film prepared by the PVA-AuNRs stacked film with different deflection angles (±15°, ±30°, ±45°) in Example 3 of the present invention. Figure 6 As can be seen in a, when the PVA-AuNRs stacked film is assembled with the fluorescent layer, it shows a high-intensity CPL because it conforms to the "matching rule" theory. This shows that when the interlayer angle of the PVA-AuNRs stacked film is set to non-0°±A90°, the certain optical activity (CD intensity) generated by it will be able to selectively absorb left-handed / right-handed fluorescence and output the corresponding right-handed / left-handed fluorescence. Figure 6 Figure b is the statistical value of the CPL intensity as the interlayer angle changes, and it is effectively fitted using a sine function. As the interlayer angle of the PVA-AuNRs stacked film changes, the CPL intensity of the circularly polarized luminescent multilayer assembled film also changes. When the deflection direction of the upper PVA-AuNRs hybrid oriented film in the PVA-AuNRs stacked film changes, the CPL direction of the circularly polarized luminescent multilayer assembled film also changes at the same time. Therefore, by regulating the interlayer angle of the PVA-AuNRs stacked film, efficient control of the CPL intensity and direction of the circularly polarized luminescent multilayer assembled film is achieved.
[0080] Figure 7 It is the CPL spectrum of the circularly polarized luminescent multilayer assembled film based on different fluorescent layers and PVA-AuNRs stacked film in Example 4 of the present invention. Figure 7It can be seen that the circularly polarized luminescent multilayer assembled films assembled from different fluorescent layers and PVA-AuNRs stacked films have different CPL colors, indicating that the present invention can adjust the CPL color of the circularly polarized luminescent multilayer assembled films by selecting fluorescent layers with different emission wavelengths, thereby achieving multicolor and white CPL covering the entire visible color range. Compared with the red fluorescent layer, the CPL obtained is relatively low because the matching degree between other fluorescent colors and the PVA-AuNRs stacked film is not so high.
[0081] Chiral optical devices with practical application value are particularly critical for controlling environmental stability such as light, temperature and durability. Therefore, the present invention conducted temperature, light and environmental durability tests on the circularly polarized luminescent multilayer assembly film of the Nile red fluorescent layer and the PVA-AuNRs stacked film with an angle of -30°. The specific results are as follows: Figures 8-10 shown.
[0082] Figure 8 The CPL spectrum changes of the circularly polarized luminescent multilayer assembled film obtained by the present invention at different use temperatures. Figure 8 It can be seen that as the ambient temperature increases, the CPL spectrum intensity of the circularly polarized luminescent multilayer assembled film begins to decrease after 120°C. When the temperature reaches 150°C, the CPL intensity decreases to 70% of the original intensity (25°C), and the glum value is 80% of the original intensity. Similarly, at 150°C, the CD intensity decreases to 80% of the original. This shows that the circularly polarized luminescent multilayer assembled film of the present invention has excellent heat resistance and stability, and the maximum operating temperature reaches 120°C without any effect on its optical properties. The thermal stability of 120~150°C also exceeds that of most chiral liquid crystal materials.
[0083] Fig. 9 The CPL spectrum changes of the circularly polarized luminescent multilayer assembled film obtained by the present invention under different UV-365nm irradiation durations. Figure 7 It can be seen that after 72 hours of UV-365nm light irradiation, the CPL spectrum of the circularly polarized luminescent multilayer assembly film has almost no change, indicating that the circularly polarized luminescent multilayer assembly film of the present invention has excellent optical stability and can greatly enhance the application value of the circularly polarized luminescent multilayer assembly film.
[0084] Fig.10 The CPL spectrum changes of the circularly polarized luminescent multilayer assembled film obtained by the present invention when placed in a standard environment (RH=50%, T=25°C) for different time periods. Fig.10 It can be seen that after being placed in the environment for 50 days, the CPL spectrum of the circularly polarized luminescent multilayer assembled film remains unchanged, indicating that the circularly polarized luminescent multilayer assembled film of the present invention has good environmental durability.
[0085] Fig.11The stress-strain curve of the PVA-AuNRs hybrid oriented film with a draw ratio of 450% for the single layer of the present invention and the physical picture showing its bendability and flexibility. Traditional optical devices are often difficult to achieve wider applications due to their high brittleness, especially in the field of wearable smart materials. In contrast, Fig.11 It can be seen that the PVA-AuNRs hybrid oriented film of the present invention exhibits impressive mechanical properties, with a strength of 216 MPa while maintaining good flexibility (elongation at break 27%), which is extremely rare in current optically active layer materials.
[0086] Fig.12 Figure a is the CPL spectrum of the circularly polarized luminescent multilayer assembly film with different fluorescent dye contents obtained in Example 5. It can be seen from the figure that the CPL intensity can also be regulated by adjusting the fluorescence intensity of the fluorescent layer (i.e., the content of the fluorescent dye). Within a certain range, the CPL intensity increases significantly with the increase of the dye content.
[0087] Fig.12 Figure b is the CPL spectrum of the circularly polarized luminescent multilayer assembled films with different AuNRs contents obtained in Example 6. It can be seen from the figure that the optical activity of the PVA-AuNRs stack can be affected by regulating the AuNRs concentration in the PVA-AuNRs stacked film, thereby achieving the regulation of the CPL of the circularly polarized luminescent multilayer assembled film. The results show that the CPL intensity increases with the increase of AuNRs concentration.
[0088] Fig.12 Figure c is the CPL spectrum of the circularly polarized luminescent multilayer assembly film with different stretching ratios obtained in Example 7. It can be seen from the figure that with the increase of the stretching ratio, the CPL intensity gradually increases, that is, the CPL intensity of the circularly polarized luminescent multilayer assembly film can be changed by adjusting the stretching ratio.
Claims
1. A circularly polarized luminescent multilayer assembled film, characterized in that: It comprises a fluorescent layer and an optically active layer stacked together; the fluorescent layer comprises a first flexible polymer film and a fluorescent dye distributed in the first flexible polymer film; the optically active layer comprises at least two layers of hybrid oriented films, the hybrid oriented films comprise a second flexible polymer film and a one-dimensional metal nanomaterial distributed in the second flexible polymer film and arranged in an oriented manner, the second flexible polymer film and the one-dimensional metal nanomaterial are both non-chiral; each layer of the hybrid oriented film is stacked and arranged at a preset deflection angle along the orientation axis direction of the one-dimensional metal nanomaterial.
2. The circularly polarized luminescent multilayer assembled film according to claim 1, characterized in that: The fluorescent dye is Nile red, coumarin, fluoroboron dipyrrole or rhodamine.
3. The circularly polarized luminescent multilayer assembled film according to claim 1, characterized in that: The first flexible polymer film is a polymethyl methacrylate film or a polyvinyl alcohol film, and the second flexible polymer film is a polyvinyl alcohol film.
4. The circularly polarized luminescent multilayer assembled film according to claim 1, characterized in that: The mass of the fluorescent dye accounts for 0.01% to 1% of the mass of the first flexible polymer film.
5. The circularly polarized luminescent multilayer assembled film according to claim 1, characterized in that: The mass of one-dimensional metal nanomaterials accounts for 0.08%~0.24% of the mass of the second flexible polymer film.
6. The circularly polarized luminescent multilayer assembled film according to claim 1, characterized in that: The one-dimensional metal nanomaterial is gold or silver.
7. The circularly polarized luminescent multilayer assembled film according to claim 1, characterized in that: The one-dimensional metal nanomaterial has a morphology of nanorods or nanowires.
8. The circularly polarized luminescent multilayer assembled film according to claim 1, characterized in that: The deflection angle between the uppermost hybrid orientation film and the lowermost hybrid orientation film is in the range of 0°~±180°, and is not 0°±A90°, where A is a constant.
9. The method for preparing the circularly polarized luminescent multilayer assembly film according to any one of claims 1 to 8, characterized in that: include: Mixing the fluorescent dye and the first polymer in a solvent to obtain a first blended solution; Drying the first mixed solution into a film to obtain a fluorescent layer; mixing a second polymer and a one-dimensional metal nanomaterial in a solvent to obtain a second blended solution; Drying the second blend solution into a film to obtain a hybrid film; axially stretching the hybrid film in one direction at a preset stretching ratio to obtain a hybrid oriented film; stacking a plurality of the hybrid oriented films at a preset deflection angle along the orientation axis to obtain an optically active layer; The fluorescent layer and the optically active layer are stacked together in sequence to obtain a circularly polarized luminescent multilayer assembly film.
10. The method for preparing the circularly polarized luminescent multilayer assembled film according to claim 9, characterized in that: The preset draft ratio is 100% to 500%.
Citation Information
Patent Citations
Chiral nanorod film with circular polarization fluorescence
CN113736450A
Flexible optical device and preparation method, modulation method and application thereof
CN114895485A
Organic-inorganic hybrid chiral film and preparation method thereof
CN118269437A
Device and method for detecting optical purity of chiral polymer
CN118276118A
Circularly polarized long afterglow material and preparation method and application thereof
CN119120003A